Decentralization and Its Influence in Determining the Direction of Public Policy as an Effort to Improve Community Welfare - Rahmat Salam; Izzatusholekha (GoAcademica Research & Publishing, 2020)
Since the fall of the New Order, the Indonesian government has moved towards a decentralized system of government. The Central Government makes policies that provide the widest possible opportunity for local governments to manage their households in order to improve welfare. This study will present an analysis of the implementation and impact of public policies made by local governments, whether they succeed or fail in their implementation, especially to improve the welfare of the community. This study also describes several alternative ways to solve problems related to policy implementation. This research is qualitative in nature using literature study methods to collect data and analyze it.